Security that is Meant to be Skin Deep: Using Ultraviolet Micropigmentation to Store Emergency-Access Keys for Implantable Medical Devices - Schechter, Stuart (2010)
Implantable medical devices, such as implantable cardiac defibrillators and pacemakers, now use wireless communication protocols vulnerable to attacks that can physically harm patients. Security measures that impede emergency access by physicians could be equally devastating. We propose that access keys be written into patients’ skin using ultraviolet-ink micropigmentation (invisible tattoos).